Distribution of the genus Cocconeis (Bacillariophyceae) along the Seogwipo coast of Jeju Island, South Korea - Joh, Gyeongje (Phytotaxa, 2021)
Cocconeis Ehrenberg species (Bacillariophyceae) are documented from benthic samples collected along the Seogwipo coast of Jeju Island, the southernmost region of Korea. The 25 taxa were identified from seaweeds, sand, and sediments, their morphological features are described, and the distributions of the taxa are summarized. Three groups of Cocconeis e.g., Cocconeis dirupta var. flexella, C. pseudomarginata var. intermedia, Cocconeis scutellum, and their similar taxa were dominant in this area. Many other Cocconeis that grows mainly along the coasts of warmer oceans were also identified. The floristic study reveals the existence of rare or retrieved species that were not well known until recently, and expands some of their geographical distributions; Cocconeis cf. callosa, C. conspicua, C. cyclophora var. decora, C. cyclophora var. meisteri, C. delicata, C. schmidtii, C. shikinensis, C. suzukii, C. voigtii. In this floristic study, 14 Cocconeis taxa are new records in South Korea.